Reconstructing the Symbolic Value of Singleness in Strengthening the Religious Character of Adolescents - Mariana; LM Carvalho (CV Edujavare Publishing, 2024)
The world of teenagers is a world with various forces and demands about freedom that require extra thought and assistance. Adolescent students are an important focus for educators and furthermore in the world of education, where in fact the world of education is still the target of worrying news. Character cultivation is an important choice in cultivating students' religious strength, one of which is through reconstructing the value of being single. The aim of this research is to find out the number of single students at Madrasah Aliyah Al Hidayah. To find out students' understanding of being single at Madrasah Aliyah Al Hidayah. To find out the reconstruction of the symbolic value of being single to strengthen the religious character of students at Madrasah Aliyah Al Hidayah. The methodology used is qualitative. Based on the results of the analysis, it can be concluded that (1) There are many single students at Madrasah Aliyah Al Hidayah due to limited data available. Some schools may not have a system that records student relationship status, so it is difficult to get accurate data about the number of single students at school. (2) The understanding of students about being single at Madrasah Aliyah Al Hidayah is described by informants as being single is not having a boyfriend, so it can it was concluded that they understood in their own language the term single. (3) The description of the reconstruction of the symbolic value of being single and strengthening religious beliefs at Madrasah Aliyah Al Hidayah was clearly explained by the results of interviews and observations which explained that their religion was stronger than when they were not single.